IMPLEMENTASI EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) - Sholeh, Muh Ibnu; Habibulloh, Muh; Sokip, S; Syafi’i, Asrop; Sahri, S; Nashihuddin, Moh; ‘Azah, Nur; Al Farisy, Fakhruddin; Sulistyorini, S (Al’ulum Jurnal Pendidikan Islam, 2025)
This study aims to analyze the implementation of PAI learning evaluation with HOTS approach. The method used in this research is a literature study method with a qualitative approach. Data were collected from various primary sources, such as scientific journals, academic books, and policy documents, as well as secondary sources in the form of seminar reports and related articles. The analysis was conducted descriptively-analytically with the stages of data classification, content analysis, and synthesis of findings. The results showed that the application of HOTS in PAI learning evaluation can improve students' critical thinking skills, especially in the aspects of analysis, synthesis, and evaluation. However, the implementation of HOTS still faces challenges such as teachers' lack of understanding of HOTS concepts, limited resources, and lack of available training. Therefore, this study recommends improving teachers' understanding through continuous training, providing adequate resources, and developing more innovative and contextualized evaluation designs. The findings of this study are expected to contribute to the development of PAI learning evaluation strategies that are more effective and relevant to the demands of education in the digital era.